Instructing in the hybrid environment: a qualitative exploration of the instructor’s perspective - Hogan, Garrett K. (My University, 2025)
Student experiences learning in a hybrid environment, where in-class seat time is limited or minimal, have been well documented. However, no similar exploration of the instructor’s experiences in the hybrid environment has occurred. The purpose of this basic qualitative study was to explore the experiences of post-secondary instructors who teach adults in a formal learning environment about their experiences teaching in a hybrid environment. The participants were recruited through social media and commercial research participant outlets. The 54 participants of this study responded to an anonymous open-ended questionnaire to detail their challenges and advantages of instructing in a hybrid environment. The participant responses were collated through an online database and batched, upon order of arrival, into batches of ten for open coding and axial coding. Between batches, the utilization of inductive thematic analysis and constant comparative analysis aligned and crystallized concepts. After six cycles of coding, the findings suggest that the instructors described their experiences as being shaped through three nexus of experience. One nexus focused on their perception of the hybrid environment. The next nexus focused on their perception of the student experience in the hybrid environment. The final nexus focused on the overall class performance. Additionally, the findings suggested that the instructors’ margin was enhanced by the organization while powering their experiences. A delimitation and limitation of the study were only one contact per participant and no participants identifying as uncomfortable in the hybrid environment respectively.
Keywords: Hybrid environment; Margin; Inductive thematic analysis; Open-ended questionnaire; Instructors’ experiences